Dissemination and Use of Point-of-Care Ultrasound by Pediatricians in Europe: A Research in European Pediatric Emergency Medicine Network Collaborative Survey. Issue 10 (24th October 2022) - Parri, Niccolò; Berant, Ron; Giacalone, Martina; Jones, Sarah Dianne; Friedman, Nir; ,
Abstract : Objective: We surveyed the dissemination and use of point-of-care ultrasound (POCUS), physician training levels, and barriers and limitations to use of POCUS among pediatricians and pediatric emergency medicine (PEM) physicians across Europe and Israel. Methods: A questionnaire was distributed through the PEM section of the European Society for Emergency Medicine and the Research in European Pediatric Emergency Medicine Network. Results: A total of 581 physicians from 22 countries fully completed the questionnaire. Participants were primarily pediatric attending physicians (34.9% [203 of 581]) and PEM attending physicians (28.6% [166 of 581]). Most of the respondents, 58.5% (340 of 581), reported using POCUS in their practice, and 61.9% (359/581) had undergone POCUS training. Point-of-care ultrasound courses represented the most common method of becoming proficient in POCUS. Overall, the Focused Assessment with Sonography in Trauma scan was the mostly taught application, with 76.3% (274 of 359). Resuscitative, diagnostic, and procedural POCUS were rated as very useful or useful by the most of respondents. The lack of qualified personnel to train (76.9% [447 of 581]), and the insufficient time for physicians to learn, POCUS (63.7% [370 of 581]) were identified as the main limitations to POCUS implementation. Conclusions: The dissemination of pediatric POCUS in the European and Israeli centers we surveyed is limited, and its applications are largely restricted to the Focused Assessment with Sonography in Trauma examination. This is likely related to lack of training programs. In contrast, the potential value of use of POCUS in PEM practice is recognized by the majority of respondents.